PENGARUH PEMBELAJARAN PENDIDIKAN IPS MI/SD TERHADAP PEMBENTUKAN KARAKTER PEDULI SOSIAL MAHASISWA PGMI UNISKA MAB BANJARMASIN - Barsihanor, Barsihanor; Hafiz, H. Abdul (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
This research aims to know the influence of learning Education sosial studies elementary school against the formation of character social care students elementary school Islamic University of Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin. This research using quantitative research approach with this type of correlation is Expost Facto. As for the data source or the respondents in this study are students elementary school Islamic University of Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin four semester. As for the data collection Techniques used are observation, documentation, and question form. Before doing research, the instrument of research first tested the validity and reliability. The next test of its homogeneity and normality. After the data collected recently done data analysis. Analysis of the data used is the formula of the percentage and simple linear regression. From the results of the research there are the influence that is experienced by sosial studies education learning toward the formation of social caring character of students is 67%, and 33% there are other factors that influence.